POTENSI DAN CABARAN PERNIAGAAN E-DAGANG PASCA COVID-19: SUATU CADANGAN PENYELESAIAN: POTENTIAL AND CHALLENGES OF E-COMMERCE BUSINESS POST COVID 19: A SOLUTION RECOMMENDATION - Baharun, Muhammad Thoriq; Mohd Balwi, Mohd Abd Wahab Fatoni (Online Journal of Islamic Management and Finance (OJIMF), 2021)
The Covid-19 epidemic has been declared as pandemic due to its increasing levels of spread and severity every single day. This indirectly affects the growth of Malaysian economy. As a result, most Malaysians, especially entrepreneurs, lost their source of income during the Covid-19 period. Therefore, the key purpose of this paper is to highlight e-commerce as the best alternative in the search for post-Covid-19 livelihoods, especially for Muslim entrepreneurs. The data obtained through library research will be used to analyze the potential and challenges of e-commerce business. The results of the study found that the potential of e-commerce business is its wider opportunities and markets as well as being able to maximize the achievement of entrepreneurial goals in Islam. While the main challenges that need to be overcome for the implementation of e-commerce business is, the competition between entrepreneurs, lack of knowledge and disciplinary problems as well as commitment of entrepreneurs.